2019
DOI: 10.1016/j.redox.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Bhlhe40 differentially regulates the function and number of peroxisomes and mitochondria in myogenic cells

Abstract: PGC-1α is a key regulator of oxidative metabolism facilitating the expression of genes critical for the function and biogenesis of the two key oxidative organelles, mitochondria and peroxisomes, in skeletal muscle (SKM) and other organs. Our recent studies have found that the transcription factor Bhlhe40 negatively regulates PGC-1α gene expression and its coactivational activity, therefore, this factor should have profound influence on the biogenesis and metabolic activity of mitochondria and peroxisomes. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Apoptosis was evaluated by using the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) Apoptosis Detection Kit (Beyotime, China) as directed by the manufacturer's instructions (Chang H. C. et al, 2019). Briefly, cells in four-chamber slides were fixed with 4% paraformaldehyde for 20 min, washed in PBS, and incubated with 75 µl of equilibration buffer for 5 min at room temperature.…”
Section: Apoptosismentioning
confidence: 99%
“…Apoptosis was evaluated by using the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) Apoptosis Detection Kit (Beyotime, China) as directed by the manufacturer's instructions (Chang H. C. et al, 2019). Briefly, cells in four-chamber slides were fixed with 4% paraformaldehyde for 20 min, washed in PBS, and incubated with 75 µl of equilibration buffer for 5 min at room temperature.…”
Section: Apoptosismentioning
confidence: 99%
“…28 A recent study demonstrated that insulin responses were highly enhanced in cells after Bhlhe40 mRNA knockdown, suggesting the importance of Bhlhe40 in the regulation of glucose oxidative metabolism. 29 The transcription factor BATF, belonging to the activator protein (AP)-1 family of transcription factors, has been shown to be predominantly expressed in cells of hematopoietic origin. 30 Moreover, BATF has been shown to act as an essential factor in immunoglobulin class-switch recombination and the regulation of metabolism and survival in CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…After being washed 4 times, the cells were incubated by with donkey anti-mouse 488 (Invitrogen, A-21202) and donkey anti-rabbit 594 (Invitrogen, A-21207) secondary antibodies for 1 h at room temperature. The cells were then rinsed 4 times and mounted on glass slides using Vectashield mounting medium (Vector, H-1500) containing DAPI [ 47 ]. Intracellular calcium ([Ca 2+ ]i) and mitochondrial calcium ([Ca 2+ ]m) were stained using Furo-2AM (Molecular Probes) and Rhod-2 (Molecular Probes), respectively, as previously described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%